Do Investors Trade around Social Rating Announcements?. (2nd October 2015) - Cellier, Alexis; Chollet, Pierre; Gajewski, Jean‐François
Abstract: This paper investigates trading around Corporate Social Responsibility (CSR) rating announcements. Focusing on CSR rating announcements made by Vigeo on European markets, we use Euronext intraday data to prove that trading volume drops sharply before announcements and increases afterwards. Willingness to trade depends mainly on prior private information and the content of the announcement. Our results show effects from disaggregated scores, but not from overall scores. More specifically, we find that some topics like business behaviour, human resources and human rights significantly influence investor trades. Environmental risk does not have an impact on trading behaviour.